Dynamic Causal Analysis between the Stock Market and Macroeconomic Variables in the USA - Chung, Rhys (2021)
This dissertation examines the dynamic relationships between the US stock market and macroeconomic variables such as consumer price index, industrial production, interest rates and money supply during the regimes of six different Federal Reserve Chairs between 1970-2020. Using Johansen’s cointegration tests and error correction techniques, the aim is to detect Granger Causality, address mixed findings about causality directions from previous literatures and investigate how these relationships change over time. The results suggest that both short- and long-term causal relationships exist. Further, there is no strict causality direction when observing the causality results inferring these bivariate causal relationships that do change over time depending on the subperiod. An interpretation of these findings is that the direction of causality can be explained based upon the Federal Reserve Chair’s monetary policy philosophy and implementation.